Effects of pulsation ratio on center temperature and drying characteristics of pineapple slices with pulsed vacuum drying - Jiang, Dalong; Li, Congcong; Lin, Zifan; Wu, Yuntian; Pei, Hongjuan (International Journal of Agricultural and Biological Engineering, 2022)
This research explored the application of pulsed vacuum technology on the drying (PVD) of pineapple slices. Influences of drying temperature and pulsed vacuum ratio (PVR) on drying characteristics and pineapple quality (color, rehydration characteristics, microstructure, and texture) were analyzed. As expected, increasing the drying temperature resulted in a higher drying rate and effective moisture diffusivity. The optimal PVR of 5:5 was beneficial in accelerating the drying rate of pineapple slices and the corresponding effective moisture diffusion coefficient (8.9601×10-10) was higher than other PVR conditions based on material center temperature. The material temperature increased during the normal pressure period and decreased rapidly when the pressure dropped to the vacuum condition, which indirectly reflected the moisture transfer that occurred during the vacuum holding period, while moisture diffusion happened during the atmospheric pressure holding period. The optimal pulsed vacuum drying process (PVR of 5:5) could expand air and water vapor and create a looser structure so as to obtain better rehydration performance (rehydration ratio (RR) was 5.43). High drying temperature led to the decrease of L* value, the increase of ΔE value, and even the formation of surface scorch at 80°C. At the same drying temperature, the color quality depended on the drying time, and the color difference increased with the extension of the drying time. The chewiness and hardness of pineapple slices dried by PVD were significantly higher than those of fresh samples, which was conducive to the chewing taste. Keywords: pulsed vacuum drying, pineapple slices, color, rehydration ratio, texture, center temperature DOI: 10.25165/j.ijabe.20221506.6665 Citation: Jiang D L, Lin Z F, Wu Y T, Pei H J, Li C C. Effects of pulsation ratio on center temperature and drying characteristics of pineapple slices with pulsed vacuum drying. Int J Agric & Biol Eng, 2022; 15(6): 242–253.